Nano-TiO2 coated single-crystal LiNi0.65Co0.15Mn0.2O2 for lithium-ion batteries with a stable structure and excellent cycling performance at a high cut-off voltage. Issue 10 (21st February 2022) - You, Longzhen; Wen, Ya; Li, Guangxin; Chu, Binbin; Wu, Jianhua; Huang, Tao; Yu, Aishui
Abstract : Nano-TiO2 coated single-crystal LiNi0.65 Co0.15 Mn0.2 O2 for lithium-ion batteries with a stable structure and excellent cycling performance at a high cut-off voltage. Abstract : Ni-rich ternary layered oxide materials have become the preferred cathode materials for lithium-ion batteries due to their high specific discharge capacity and low price. However, the hierarchical structure of the materials will suffer from an inevitable structural collapse during the battery cycling process, especially at high cut-off voltage. This collapse arises from intergranular cracking and irreversible phase transformation caused by serious side reactions accompanied by a serious specific discharge capacity decline. Preparing single-crystalline materials is a key strategy to solve the problem of intergranular cracking and interface side reactions in the electrochemical cycling process of Ni-rich ternary layered oxide materials. Here, a single crystal LiNi0.65 Co0.15 Mn0.2 O2 (S-NCM65) with a diameter of 3–5 μm was synthesized, and its surface was modified by nano-TiO2 (5TS-NCM65) to enhance the surface stability and further improve the cycling performance at room temperature and elevated temperature. The capacity retention of S-NCM65 is only 86.03% after 200 cycles at 25 °C from 3.0 to 4.5 V and at a current density of 1C (1C = 200 mA g −1 ); 5TS-NCM65 has capacity retention as high as 94.16%. Under similar conditions, the capacity retention of S-NCM65 is only 87.59% after 125 cycles when the temperature is increased to 55 °C, while the capacity retention of 5TS-NCM65 is 93.31%. Moreover, a series of characterization experiments show that treating the surface of single crystal materials with nano-TiO2 can improve the reversibility of H2/H3 phase transformation during the electrochemical process, thus significantly inhibiting intergranular cracks and alleviating side reactions at the electrode/electrolyte interface.